How and why does willow biochar increase a clay soil water retention capacity?. (December 2018) - Rasa, Kimmo; Heikkinen, Jaakko; Hannula, Markus; Arstila, Kai; Kulju, Sampo; Hyväluoma, Jari
Abstract: Addition of biochar into a soil changes its water retention properties by modifying soil textural and structural properties. In addition, internal micrometer-scale porosity that is able to directly store readily plant available water affects soil water retention properties. This study shows how precise knowledge of the internal micrometer-scale pore size distribution of biochar can deepen the understanding of the biochar-water interactions in soils. The micrometer-scale porosity of willow biochar was quantitatively and qualitatively characterized using X-ray tomography, 3D image analysis and Helium ion microscopy. The effect of biochar application on clay soil water retention was studied by conventional water retention curve approach. The results indicate that the internal pores of biochar, with sizes of at 50 and 10 μm (equivalent pore diameter), increased soil porosity and the amount of readily plant available water. After biochar addition, changes in soil porosity were detected at pore size regimes 5–10 and 25 μm, i.e. biochar pore sizes multiplied by factor 0.5. The detected pore size distribution of biochar does not predict directly (1:1 compatibility) the changes observed in the soil moisture characteristics. It is likely that biochar chemistry and pore morphology affect biochar-water interactions via e.g. surface roughness and contact angle. In addition, biochar induced changes in soil structure and texture affected soil moisture characteristics. However, the approach presented is an attractive pathway to more generalized understanding on how and why biochar internal porosity affects soil moisture characteristics. Graphical abstract: Highlights: Biochar porosity was studied using X-ray tomography and Helium ion microscopy. Biochar had bimodal pore structure with local maxima at 50 and 10 μm. Detected biochar porosity affected soil water retention via direct mechanism. Soil porosity at regime of 25 and 5–10 μm increased due to biochar addition. The role of micrometer-scale pores of biochar on soil water retention was highlighted.